The SAMI galaxy survey: Mass and environment as independent drivers of galaxy dynamics. Issue 2 (15th September 2021) - van de Sande, Jesse; Croom, Scott M; Bland-Hawthorn, Joss; Cortese, Luca; Scott, Nicholas; Lagos, Claudia D P; D'Eugenio, Francesco; Bryant, Julia J; Brough, Sarah; Catinella, Barbara; Foster, Caroline; Groves, Brent; et al.
ABSTRACT: The kinematic morphology–density relation of galaxies is normally attributed to a changing distribution of galaxy stellar masses with the local environment. However, earlier studies were largely focused on slow rotators; the dynamical properties of the overall population in relation to environment have received less attention. We use the SAMI Galaxy Survey to investigate the dynamical properties of ∼1800 early and late-type galaxies with log ( M ⋆ / M ⊙ ) > 9.5 as a function of mean environmental overdensity (Σ5 ) and their rank within a group or cluster. By classifying galaxies into fast and slow rotators, at fixed stellar mass above log ( M ⋆ / M ⊙ ) > 10.5, we detect a higher fraction (∼3.4σ) of slow rotators for group and cluster centrals and satellites as compared to isolated-central galaxies. We find similar results when using Σ5 as a tracer for environment. Focusing on the fast-rotator population, we also detect a significant correlation between galaxy kinematics and their stellar mass as well as the environment they are in. Specifically, by using inclination-corrected or intrinsic λ _R_e values, we find that, at fixed mass, satellite galaxies on average have the lowest λ _ R_e, intr, isolated-central galaxies have the highest λ _ R_e, intr, and group and cluster centrals lie in between. Similarly, galaxies in high-density environments have lower mean λ _ R_e, intr values as compared to galaxies at low environmental density. However, at fixed Σ5, the mean λ _ R_e, intr differences for low and high-mass galaxies are of similar magnitude as when varying Σ5 (Δ λ _ R_e, intr 0.05, with σrandom = 0.025, and σ syst < 0.03). Our results demonstrate that after stellar mass, environment plays a significant role in the creation of slow rotators, while for fast rotators we also detect an independent, albeit smaller, impact of mass and environment on their kinematic properties.